Nesfatin-1 alleviates extrahepatic cholestatic damage of liver in rats - ERZİK, CAN (ASSOC BASIC MEDICAL SCI FEDERATION BOSNIA & HERZEGOVINA SARAJEVO, 2016)
Obstructive jaundice (OJ) can be defined as cessation of bile flow into the small intestine due to benign or malignant changes. Nesfatin-1, recently discovered anorexigenic peptide derived from nucleobindin-2 in hypothalamic nuclei, was shown to have anti-inflammatory and antiapoptotic effects. This study is aimed to investigate the therapeutic effects of nesfatin-1 on OJ in rats. Twenty-four adult male Wistar-Hannover rats were randomly assigned to three groups: sham (n = 8), control (n = 8), and nesfatin (n = 8). After bile duct ligation, the study groups were treated with saline or nesfatin-1, for 10 days. Afterward, blood and liver tissue samples were obtained for biochemical analyses, measurement of cytokines, determination of the oxidative DNA damage, DNA fragmentation, and histopathologic analyses. Alanine aminotransferase and gamma-glutamyl transferase levels were decreased after the nesfatin treatment; however, these drops were statistically non-significant compared to control group (p = 0.345, p = 0.114). Malondialdehyde levels decreased significantly in nesfatin group compared to control group (p = 0.032). Decreases in interleukin-6 and tumor necrosis factor-a levels from the liver tissue samples were not statistically significant in nesfatin group compared to control group. The level of oxidative DNA damage was lower in nesfatin group, however this result was not statistically significant (p = 0.75). DNA fragmentation results of all groups were similar. Histopathological examination revealed that there was less neutrophil infiltration, edema, bile duct proliferation, hepatocyte necrosis, basement membrane damage, and parenchymal necrosis in nesfatin compared to control group. The nesfatin-1 treatment could alleviate cholestatic liver damage caused by OJ due to its anti-inflammatory and antioxidant effects.
Keywords: Obstructive jaundice; oxidative stress; hepatic damage; cholestasis; DNA fragmentation; BILE-DUCT OBSTRUCTION; OXIDATIVE STRESS; DEOXYRIBONUCLEIC-ACID; LIPID-PEROXIDATION; MELATONIN; JAUNDICE; INJURY; ANTIOXIDANTS; HEPATOCYTES; MECHANISMS